2003
DOI: 10.1002/psc.541
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity scanning in the mapping of the peptide receptor interface of class II G protein—coupled receptors

Abstract: The family of G protein-coupled receptors constitutes about 50% of the therapeutic drug targets used in clinical medicine today, although the mechanisms of ligand binding, activation and signal transduction for G protein-coupled receptors are not yet well defined. This review discusses ongoing research using the photoaffinity scanning method to map the bimolecular interface between class II G protein-coupled receptors and their ligands. Furthermore the available computer model of class II peptide ligand dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 185 publications
0
17
0
Order By: Relevance
“…The crystal structure of the PTH1R extracellular domain-PTH(15-34) complexes provides direct evidence for the model that the C-terminal domain of the ligand binds to the N terminus of the receptor, thus positioning the N terminus of the ligand at a favorable distance to allosterically activate the J-domain of the receptor (52). Therefore, it is interesting to compare the data from photoaffinity cross-linking of PTH1R (22)(23)(24)(25)(53)(54)(55)(56)(57)(58)(59)(60) with those of CRFR1. Similar to our finding that residues 16 and 17 of sauvagine cross-link to the J-domain of CRFR1, residues within the C terminus of PTH , such as 19 and 27, are reported to cross-link to the second transmembrane domain and within the first extracellular loop, respectively; both are within the J-domain of PTH1R (58).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of the PTH1R extracellular domain-PTH(15-34) complexes provides direct evidence for the model that the C-terminal domain of the ligand binds to the N terminus of the receptor, thus positioning the N terminus of the ligand at a favorable distance to allosterically activate the J-domain of the receptor (52). Therefore, it is interesting to compare the data from photoaffinity cross-linking of PTH1R (22)(23)(24)(25)(53)(54)(55)(56)(57)(58)(59)(60) with those of CRFR1. Similar to our finding that residues 16 and 17 of sauvagine cross-link to the J-domain of CRFR1, residues within the C terminus of PTH , such as 19 and 27, are reported to cross-link to the second transmembrane domain and within the first extracellular loop, respectively; both are within the J-domain of PTH1R (58).…”
Section: Discussionmentioning
confidence: 99%
“…Klose et al (24) reported on the binding behavior of N-terminally truncated urocortins to soluble receptor N-termini. They proposed a three-domain binding model, in that the urocortin C-terminus (aa [32][33][34][35][36][37][38][39][40] and the N-terminal part (aa 1-21) are organized as two segregated binding domains. Moreover, the N-terminal domain (aa 1-21) also consists of two segregated sites; one is responsible for receptor activation (aa 1-11) and the other (aa [12][13][14][15][16][17][18][19][20][21] for ligand binding at the receptor N-terminus.…”
mentioning
confidence: 99%
“…This first interaction positions the N-terminal region of the peptide such that it activates the receptor via a second interaction with the receptor's juxtamembrane "core" domain, comprising the transmembrane helices and connecting loops. The nature of the first interaction has been investigated via a number of mutagenic and cross-linking studies (Mannstadt et al, 1998;Gensure et al, 2001;Pham and Sexton, 2004) and more recently has been the focus of several structural studies that defined the structures of the peptidebound N domains of the receptors for corticotropin-releasing factor, pituitary adenylyl cyclase-activating polypeptide, glucose-dependent insulinotropic peptide (GIP), glucagon-like peptide-1 (GLP-1) and, very recently, PTH itself (Grace et al, …”
mentioning
confidence: 99%